Scientific farm animal production : an introduction to animal science - Field, Thomas G. [ (Thomas Gordon)] (Prentice Hall, 2012)
Synopsis: The ninth edition of this best-selling book examines the biological principles, scientific relationships, and management practices of livestock production. Blending the discussion of science, disciplines and industries, it effectively introduces readers to Animal Science using a breadth and depth that is unparalleled. Following a logical organization, it first discusses animal products, then basic biological principles (growth, genetics, reproduction, nutrition, health, etc.) and finally the feeding, breeding and management of primary livestock industries. It also gives readers insight into the societal issues surrounding the livestock industry and an overview of the careers and opportunities available within the field